Dynamical masses of early-type galaxies: a comparison to lensing results and implications for the stellar initial mass function and the distribution of dark matter - Thomas, J; Saglia, R; Bender, R; Thomas, D; Gebhardt, K; Magorrian, J; Corsini, E; Wegner, G; Seitz, S (2011)
This work aims to study the distribution of the luminous and dark matter in Coma early-type galaxies. Dynamical masses obtained under the assumption that mass follows light do not match with the masses of strong gravitational lens systems of similar velocity dispersions. Instead, dynamical fits with dark matter haloes are in good agreement with lensing results. We derive mass-to-light ratios of the stellar populations from Lick absorption line indices, reproducing well the observed galaxy colours. Even in dynamical models with dark matter haloes the amount of mass that follows the light increases more rapidly with the galaxy velocity dispersion than expected for a constant stellar initial mass function (IMF). While galaxies around σeff≈ 200kms-1 are consistent with a Kroupa IMF, the same IMF underpredicts luminous dynamical masses of galaxies with σeff≈ 300kms-1 by a factor of 2 and more. A systematic variation in the stellar IMF with the galaxy velocity dispersion could explain this trend with a Salpeter IMF for the most massive galaxies. If the IMF is instead constant, then some of the dark matter in high-velocity-dispersion galaxies must follow a spatial distribution very similar to that of the light. A combination of both, a varying IMF and a component of dark matter that follows the light is possible as well. For a subsample of galaxies with old stellar populations, we show that the tilt in the Fundamental Plane can be explained by systematic variations of the total (stellar + dark) mass inside the effective radius. We tested commonly used mass estimator formulae, finding them accurate at the 20-30 per cent level. © 2011 The Authors Monthly Notices of the Royal Astronomical Society © 2011 RAS.